1996
DOI: 10.1136/oem.53.7.484
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and fungal flora of dust deposits in a pig building.

Abstract: Objectives-The purpose of the study was to investigate the bacterial and fungal flora of dust deposits in a newly built pig grower finisher building. Viable bacterial counts and microbial species found in a barn which had never housed pigs were compared with those in a barn housing 144 pigs. Methods-The quantitative streak plate method was used to measure viable bacterial counts on nutrient agar or sheep blood agar. Viable bacterial counts of the dust deposits were expressed as the number of colony forming uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…One of the sources of microorganisms (bacteria in particular) in swine barns could the animals themselves, emitting them with the exhaled air, rubbed off epidermis or faeces (Martin et al 1996). Contrary to other researchers, who correlated the higher bacterial concentrations in swine barn bioaerosol with the increase in herd size (Duchaine et al 2000), in this study, higher concentrations of bacteria were observed in smaller herds.…”
Section: Discussionmentioning
confidence: 63%
“…One of the sources of microorganisms (bacteria in particular) in swine barns could the animals themselves, emitting them with the exhaled air, rubbed off epidermis or faeces (Martin et al 1996). Contrary to other researchers, who correlated the higher bacterial concentrations in swine barn bioaerosol with the increase in herd size (Duchaine et al 2000), in this study, higher concentrations of bacteria were observed in smaller herds.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies revealed a ubiquitous presence of gramnegative bacteria in PM sampled from animal buildings, with the following genera identified: Acinetobacter, Bacteroides, Enterobacter, Moraxella, Pasteurella, Pseudomonas, and Vibrio (Martin et al, 1996;Predicala et al, 2002;Nehme et al, 2008). However, gram-negative bacteria may only account for a small fraction of the total airborne bacteria in animal buildings.…”
Section: Resultsmentioning
confidence: 99%
“…With culture-based methods, the following fungal genera have previously been identified in CAFOs: Absidia, Alternaria, Aspergillus, Cladosporium, Mucor, Penicillium, Rhizopus, and Scopulariopsis (Martin et al, 1996;Seedorf et al, 1998;Predicala et al, 2002). However, the majority of airborne fungal spores can be nonculturable (Rylander and Etzel, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…A higher culturable Gram-positive flora than Gram-negative is considered to be typical of most environments. 7,22,59,60 Most studies on exposure to cotton dust have focused on airborne levels of endotoxin and Gramnegative bacteria. However, the vast majority of bacteria isolated from cotton dust are Gram-positive.…”
Section: Discussionmentioning
confidence: 99%